2002
DOI: 10.1002/j.2161-007x.2002.tb00210.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religious Beliefs in Coping With Chronic Illness

Abstract: The authors examined the ways in which 40 women with chronic illnesses (rheumatoid arthritis, osteoporosis, multiple sclerosis, systemic lupus erythematosus, or a combination of these disorders) used religious beliefs as a means of coping with their illnesses, The participants, all between the ages of 28 and 79 years, were interviewed about the role religious beliefs played in their experiences and the ways in which they made meaning in their lives or coped with their illnesses. The majority of the women repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 30 publications
2
33
0
2
Order By: Relevance
“…This is consistent with the results of other studies (Gordon, 2002;Nichols, & Hunt, 2011), which emphasize the positive value of spiritual resources in coping more effectively with the symptoms of the illness. The results indicate that emotional support seeking is related with a higher perceived of importance of all resources (especially vital and spiritual).…”
Section: Significance Of Vital and Spiritual Resources In Patientssupporting
confidence: 92%
“…This is consistent with the results of other studies (Gordon, 2002;Nichols, & Hunt, 2011), which emphasize the positive value of spiritual resources in coping more effectively with the symptoms of the illness. The results indicate that emotional support seeking is related with a higher perceived of importance of all resources (especially vital and spiritual).…”
Section: Significance Of Vital and Spiritual Resources In Patientssupporting
confidence: 92%
“…Given all of the evidence of the mental health benefits of prayer and other spiritual practices (Connerley, 2003;Finney & Malony, 1985;Gordon et al, 2002;Poloma & Pendleton, 1989), therapists may be remiss in not considering prayer as a possible intervention, because prayer in the proper context may promote client welfare. However, as Kennedy and Charles (2001) stated, "sensible counselors will not quickly apply purely spiritual solutions-such as prayer and fasting-to problems that usually have deeper and more complicated origins" (p. 127).…”
Section: Discussionmentioning
confidence: 97%
“…"Religious or Spiritual Problem" was added to the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders (4th ed., DSM-IV; American Psychiatric Association [APA], 1994) and continued in the text revision of DSM-IV (APA, 2000). Moreover, the number of studies being conducted to evaluate the link between people's spirituality and mental health and between clients' spirituality and effective psychotherapy (e.g., Gordon, Feldman, Crose, Schoen, Griffing, & Shankar, 2002;Wade & Worthington, 2003) indicates that there is presently a more amiable posture between secular psychology and religion than was historically evidenced.…”
Section: Prevalence and Beliefs About Prayer In Counselingmentioning
confidence: 97%
“…However, the interpretation and expectation of suffering is shaped by many factors. In the last decade, social scientists have focused on social-cultural aspects of suffering and have found that religious and personal beliefs change the perception of suffering and therefore the interpretation of suffering (Fulford, 2017; Tzounis, Kerenidi, Daniil, Hatzoglou, Kotrotsiou & Gourgoulianis, 2016; Kéri, 2015;Koenig, 2012;Balboni, Vanderwerker, Block, Paulk, Lathan, Peteet & Prigerson, 2007;Tarakeshwar, Vanderwerker, Paulk,Pearce, Kasl & Prigerson, 2006; Wilkinson, 2001;Williams, Jerome, White & Fisher, 2006;Gordon, Feldman, Crose, Schoen, Griffing & Shankar, 2002). The purpose of this paper is to examine the influence of religion and culture on the meaning of suffering in Zabbaleen women of Cairo, Egyptfrom a healthcare perspective in the context of having Hepatitis C. This community lives in a society that incorporates traditional Egyptian beliefs and strong Christian religion in a larger society of Islam.…”
mentioning
confidence: 99%